OUTCOMES OF UNIVERSAL EXERCISE UNIT (UEU) IN COMBINATION WITH CONVENTIONAL PHYSICAL THERAPY ON TRUNK CONTROL IMPROVEMENT IN SPASTIC AND ATHETOID TYPE CEREBRAL PALSY CHILDREN - Mubashra Khalid; Farjad Afzal; Hafiz Muhammad Asim (Journal of University Medical & Dental College, 2016)
ABSTRACT: Objective: To measure outcomes of Universal exercise unit in combination of other therapies on trunk control of cerebral palsy. Material and Methods: A sample of 25 children were selected and a baseline measurement (pre-intervention) was taken by using trunk impairment (TIS) scale three to ten days before the interventions. Interventions were carried out 5 days in a week for one hour daily. A postintervention measurement was taken after the 06 months. Results: In this study descriptive statistical tools were used to analyze the data. Mean Preintervention TIS score was 10.60±2.64. Mean post-intervention TIS score was 15.04±3.63. Mean change in TIS score after 06 months was 4.44±3.15. Mean of pre-intervention score and post-intervention score are compared by using Wilcoxon signed rank test, p=0.000 showing significant change between pre-intervention and post-intervention. Conclusion: The Conclusion was that Universal exercise unit in combination of conventional physical therapies have significant effects to improve the trunk control of children diagnosed with cerebral palsy.